2016
DOI: 10.1093/jmcb/mjw045
|View full text |Cite
|
Sign up to set email alerts
|

AXL receptor signalling suppresses p53 in melanoma through stabilization of the MDMX–MDM2 complex

Abstract: Deregulation of the tyrosine kinase signalling is often associated with tumour progression and drug resistance, but its underlying mechanisms are only partly understood. In this study, we investigated the effects of the receptor tyrosine kinase AXL on the stability of the MDMX-MDM2 heterocomplex and the activity of p53 in melanoma cells. Our data demonstrated that AXL overexpression or activation through growth arrest-specific 6 (Gas6) ligand stimulation increases MDMX and MDM2 protein levels and decreases p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…Interestingly, a recent finding showed that AXL suppressed p53 in melanoma through stabilization of the MDMX-MDM2 complex. AXL activation stabilized MDMX via a post-translational modification that involved phosphorylation of MDMX [ 38 ]. Collectively, these data demonstrate that AXL negatively regulates p53 expression by at least two mechanisms: (1) TP53 transcription inhibition, irrespective of p53 mutation status; (2) stabilization of the MDMX-MDM2 complex.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent finding showed that AXL suppressed p53 in melanoma through stabilization of the MDMX-MDM2 complex. AXL activation stabilized MDMX via a post-translational modification that involved phosphorylation of MDMX [ 38 ]. Collectively, these data demonstrate that AXL negatively regulates p53 expression by at least two mechanisms: (1) TP53 transcription inhibition, irrespective of p53 mutation status; (2) stabilization of the MDMX-MDM2 complex.…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma, a reduction of the p53 protein levels is commonly reported [ 3 , 11 ••, 12 ]. The downregulation of TP53 gene may be due to several mechanisms [ 62 64 ]: inactivation of p14 CDKN2A causing MDM2 overexpression, or increased stability of MDM2-4 proteins induced by activation of the receptor tyrosine kinase AXL, or TP53 gene silencing through genetic changes (mostly, mutations) or epigenetic deregulations (Fig. 1 ).…”
Section: Tp53 Genementioning
confidence: 99%
“…In fact, in these cells miR-18b expression is frequently downmodulated by hypermethylation; MDM2 is a molecular target of miR-18b, and the downmodulation of this miR in melanoma cells is responsible for MDM2 upmodulation, with consequent p53 inactivation [ 84 ]. Another mechanism stimulating MDM2 expression in melanoma cells is related to AXL receptor signaling [ 85 ].…”
Section: Molecular Abnormalitiesmentioning
confidence: 99%